Pengaruh Literasi Keuangan Syariah, Kemudahan Aplikasi dan Kepercayaan terhadap Minat Mahasantri Ma’had Al-Jami’ah UIN Fatmawati Sukarno Bengkulu menggunakan M-Banking Bank Syariah Indonesia - Fatmawati, Dinda; B, Idwal; Cahyono, Andi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The purpose of this study was to determine the influence of sharia financial literacy, application convenience, and trust on the interest of Ma'had Al-Jami'ah UIN Fatmawati Sukarno Bengkulu students in using M-Banking Bank Syariah Indonesia. The research method used was quantitative with a primary data collection technique in the form of questionnaires distributed to 75 respondents. The data analysis technique used was the Partial Least Square (PLS) method with the help of the SmartPLS 4.1.1.6 application. The results showed that simultaneously, based on the bootstrapping results and the coefficient of determination (R2) value, the independent variables in the model as a whole had a significant effect on the dependent variable, with an R2 value of 0.835. Meanwhile, in the partial test, the sharia financial literacy variable did not have a significant effect on the interest of students in using M-Banking Bank Syariah Indonesia. This was proven by the t-statistic value of 0.410 < t-table of 1.96. The application convenience variable had a positive and significant effect on the interest of students in using M-Banking Bank Syariah Indonesia. This was proven by the t-statistic value of 3.629 > t-table of 1.96. The trust variable did not have a significant effect on the interest of students in using M-Banking Bank Syariah Indonesia. This was proven by the t-statistic value of 0.273 < t-table of 1.96. Based on the results of data analysis in this study, the application convenience variable has a significant effect on the Technology Acceptance Model (TAM) theory, which states that individuals tend to adopt new technologies if the system is considered free from heavy effort (effortless).